Teori Uses and Gratifications terhadap Kecenderungan Kecanduan Informasi dan Hiburan di Sosial Media TikTok pada Generasi Z - Meliya Jayanti; Syifa Amelia; M Iqbal Hilmi; Dieo Kusumaatmaja; M Adnan Reihan; H Eko Purwanto (CV. ITTC INDONESIA, 2025)
This study is a literature review aimed at analyzing the relationship between the Uses and Gratifications theory and the tendency toward information and entertainment addiction on the TikTok social media platform among Generation Z. TikTok, as a highly popular short-form video platform, has become a medium capable of fulfilling various user needs, such as entertainment, information, social interaction, and self-identity formation. Using the Uses and Gratifications approach, this study examines five relevant journals that explore the motives, needs, and satisfaction of TikTok users. The findings reveal that Generation Z actively and selectively uses TikTok to fulfill their cognitive, affective, social, and practical needs. The personalized algorithm and diverse content make TikTok highly adaptive to user preferences. However, the high intensity of use also has the potential to trigger addiction, especially when these needs are constantly fulfilled instantly. Thus, the Uses and Gratifications theory not only explains the motives behind TikTok usage but also provides insight into the risks of excessive use among this digital native generation.